Implementation of field oriented control on brushless DC motors for UAV application - Lao, Jonathan U. (Animo Repository, 2021)
UAV technology is growing at a fast-paced pace with development and innovations being made around the world. However, limitations on its flight endurance emerge due to the finite energy storage capacity. With the propulsion system being the main component of the drone that requires most of the power, its efficiency is something considerable to look into. With this, the study investigates the implementation of field oriented control for UAV application. A PLL estimator is developed for sensorless field oriented control and demonstrated via simulation. This enables the system to maximize torque efficiency due to the control system. In addition, a testbench for the measurement of the performance of an ESC-motor pair is designed. Based on the current draw of the system and the thrust capacity, a relative comparison of efficiency is made. It was seen in the simulation results that the estimated rotor speed and position are accurate when compared to the measured results of the sensor blocks. The designed test bench was able to record the thrust and current readings for a linear throttle test and simulated flight plan test where it was found that a fabricated ESC is more efficient that the chosen commercial ESC.